Scripted control of technological process of the sugar prodaction - Kyshenko, Vasil; Sych, Maryna (Kyshenko, V. Scripted control of technological process of the sugar prodaction / V. Kyshenko, M. Sych // Scientific enquiry in the contemporary world: theoretical basiсs and innovative approach. - B&M Publishing (San Francisco, California, USA), 2016. - №7. – P. 215-219., 2016)
З точки зору сценаріїв оптимізації показників якості, ефективності використання матеріальних та енергетичних ресурсів, а також продуктивності виробництва в статті сформульована задача керування основними технологічними процесами цукрового виробництва. Створено сценарії керування та представлена реалізація А-сценарію керування технологічним комплексом цукрового заводу.There is formulated the problem of management of major technological processes of sugar production, from the perspective of optimization script of quality indicators, efficiency use of material and energy resources, and productivity. There is created scripts of control and represented an implementation of the A-script control technological complex of sugar refinery.
Keywords: сценарний підхід; об’єкт керування; цукрове виробництво; сценарій; сценарный подход; объект управления; сахарное производство; сценарий; scenario approach; object control; sugar production; script; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка